2022
DOI: 10.3389/fpubh.2022.798686
|View full text |Cite
|
Sign up to set email alerts
|

Export Expansion May Increase Adult Illness and Injury: A Quasi-Natural Experiment on China's Accession to the World Trade Organization

Abstract: PurposeExports can boost the economy, but may also cause harm to health through, for example, increased pollution and working hours. Although academic research extensively covers the impact of trade on health, few studies examine the mechanisms through which export expansion affects adult illness or injury within the past 4 weeks (illness/injury).MethodWe utilized China's entry into the World Trade Organization (WTO) as a quasi-natural experiment to investigate the relationship between export expansion and adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Using data from China's Health and Nutrition Survey, Feng et al (2021) found that the reduction in export tariffs in China resulted in increased income, leading to improved health among working-age adults [11]. Based on the export expansion resulting from China's accession to the WTO, Chen et al (2022) found that export expansion has a significant positive impact on adult diseases/injuries in China [12].…”
Section: Introductionmentioning
confidence: 99%
“…Using data from China's Health and Nutrition Survey, Feng et al (2021) found that the reduction in export tariffs in China resulted in increased income, leading to improved health among working-age adults [11]. Based on the export expansion resulting from China's accession to the WTO, Chen et al (2022) found that export expansion has a significant positive impact on adult diseases/injuries in China [12].…”
Section: Introductionmentioning
confidence: 99%